Tempe as superior functional antioxidant food: From biomechanism to future development of soybean-based functional food - Reggie Surya; Nurlinah Amalia; William Ben Gunawan; Nurpudji Astuti Taslim; Marwan Ghafoor; Nelly Mayulu; Hardinsyah Hardinsyah; Rony Abdi Syahputra; Felicia Kartawidjajaputra; Gianluca Rizzo; Raymond Rubianto Tjandrawinata; Dionysius Subali; et al. (Pensoft Publishers, 2024)
Foods that have nutritional value along with additional health advantages are referred to as functional foods. Fruits, vegetables, and spices are rich sources of antioxidants, which can help prevent damage from free radicals and environmental stress. It has been demonstrated that consuming foods high in antioxidants lowers the risk of degenerative diseases such as cancer, emphysema, immunological deficiencies, respiratory disorders, heart disease, and stroke. It also lowers the risk of Parkinson's disease and other inflammatory conditions. Traditional Indonesian fermented soybean-based food products, or soybeans and known as "tempe", have been associated with a host of health benefits, including a lower risk of cardiovascular disease, a lower risk of cancer, improved bone health, and enhanced immunological function. This article investigates tempe's potential as a meal with antioxidant properties and suggests a mechanism via which it can trigger the Nrf2-mediated antioxidant response. The study offers insights into the potential applications, development, and potentiation of tempe by synthesizing potential biomolecular pathways for its antioxidant actions at the cellular level.